Glutamate Scavenging as a Neuroreparative Strategy in Ischemic Stroke - Kaplan-Arabaci, Oykum; Acari, Alperen; Ciftci, Pinar; Gozuacik, Devrim (Frontiers in Pharmacology, 2022)
Stroke is the second highest reason of death in the world and the leading cause of disability. The ischemic stroke makes up the majority of stroke cases that occur due to the blockage of blood vessels. Therapeutic applications for ischemic stroke include thrombolytic treatments that are in limited usage and only applicable to less than 10% of the total stroke patients, but there are promising new approaches. The main cause of ischemic neuronal death is glutamate excitotoxicity. There have been multiple studies focusing on neuroprotection via reduction of glutamate both in ischemic stroke and other neurodegenerative diseases that ultimately failed due to the obstacles in delivery. At that point, systemic glutamate grabbing, or scavenging is an ingenious way of decreasing glutamate levels upon ischemic stroke. The main advantage of this new therapeutic method is the scavengers working in the circulating blood so that there is no interference with the natural brain neurophysiology. In this review, we explain the molecular mechanisms of ischemic stroke, provide brief information about existing drugs and approaches, and present novel systemic glutamate scavenging methods. This review hopefully will elucidate the potential usage of the introduced therapeutic approaches in stroke patients.